PERBANDINGAN METODE DENYUT JANTUNG DENGAN FAKTORIAL UNTUK MENGUKUR ENERGY EXPENDITURE PADA DOMBA KERJA LAKTASI - Dwatmadji Dwatmadji (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
The use of conventional gaseous exchange methods for measuring animal energy expenditure is technically difficult and not generally feasible for animals working under field conditions. This experiment was held to study comparison of heart rate and factorial method measurements for predicting energy expenditure in working lactating Merino ewes. The ewes used were two years old, having similar liveweight and body condition, and given ad libitum mixed feed of sorghum and lucerne hay containing 13% of crude protein. The “Working” eweswas placed on modified horse treadmill with speed of 0.9 m second-1, 3 hours, load of 10% liveweight, and 0o incline; whereas the “Control” ewes were standing adjacent to opposite group. Energy expenditure was done using Heart-rate method and Factorial method. Heart rate was through measuring air bubble pulse created within the stream of heparinised saline in the jugular catheter. It was observed that mean energy expenditure estimated by using the Heart-Rate method was higher than that derived by the Factorial method and energy expenditure of Working ewes was higher than that of their Control counterparts, during both Work and Recovery periods.